Quality of Life Assessment in Patient who Underwent Chemotherapy in Gynaecologic Oncology Division: Penilaian Kualitas Hidup pada Pasien yang menjalani Kemoterapi di Divisi Onkologi Ginekologi - Hariyono Winarto; William Halim (Indonesian Socety of Obstetrics and Gynecology, 2020)
Abstract Objective: To determine the quality of life in cancer patients who underwent chemotherapy treatment.Methods: A cross-sectional study was conducted from June to August 2019. Patients with cancer, who had undergone chemotherapy and willing to participate were included in this study. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-30 (EORTC QLQ–30) questionnaire was used as the measurement tool. The patients were grouped into three groups based on the cycles of chemotherapy.Results: Sixty three responders participated in the study. As the treatment progressed, there was a signifi cant decrease in Global Health Status (GHS) and social function. In symptom scales, there was a signifi cant increase in nausea and vomiting, pain, and insomnia.Conclusions: There was a decrease in the quality of life in patients with gynecological cancer who underwent chemotherapy in dr. Cipto Mangunkusumo National General Hospital. This result should be an evaluation for the healthcare provider to implement a holistic approach in managing cancer patients.Keywords: chemotherapy, gynaecological cancer, quality of life. Abstrak Tujuan: Untuk menilai kualitas hidup pasien kanker yang menjalani kemoterapi.Metode: Penelitian dilakukan dengan metode potong lintang, dilakukan dari Juni hingga Agustus 2019. Semua pasien dengan kanker yang menjalani kemoterapi dan bersedia mengikuti penelitian diikutsertakan dalam penelitian ini. Penilaian dilakukan menggunakan kuisioner dari The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-30 (EORTC QLQ- 30) digunakan. Pasien dikelompokkan menjadi 3 kelompok berdasarkan siklus kemoterapinya.Hasil: Terdapat 63 pasien yang berpartisipasi dalam penelitian ini. Seiring pengobatan, terdapat penurunan signifikan pada global health status (GHS) dan fungsi sosial. Gejala yang meningkat secara signifi kan antara lain mual dan muntah, nyeri, dan insomnia.Kesimpulan: Terdapat penurunan kualitas hidup pada pasien kanker ginekologi yang menjalani kemoterapi di Rumah Sakit Dr. Cipto Mangunkusumo. Hasil penelitian ini menjadi evaluasi untuk penyedia layanan kesehatan agar dapat menangani pasien kanker secara holistik.Kata kunci: kanker ginekologi, kemoterapi, kualitas hidup.